Pendampingan Penerapan Hazard Analysis Critical Control Point (HACCP) Pada UMKM Pengolahan Abon Lele - Ernawati, Ernawati; Ainiyah, Roisatul; Palupi, Hapsari Titi; Syarwani, Muhammad; Hasyim, Mochamad; Huda, Miftahul; Ahwan, Zainul; Hakim, Lukman; Sulhan, Muhammad; Swasono, Muh Aniar Hari (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Suole MSME is a catfish floss producer committed to enhancing product quality through the implementation of the Hazard Analysis and Critical Control Point (HACCP) system.  Implementation is carried out by development and verification of the production process flow diagram, hazard identification, determination of Critical Control Points (CCPs), and establishment of critical limits. This community service activity aimed to provide knowledge and assistance in HACCP implementation to enhance food safety, product quality, and competitiveness. The activity was conducted from October to December 2024 at UMKM Suole, and included interviews, field observations, and HACCP assistance and analysis. The results show that the catfish floss production process involves several critical stages that require monitoring, such as raw material reception, meat separation, frying, and packaging. Hazard identification and determination of Critical Control Points (CCPs) have been carried out to prevent biological, chemical, and physical contamination. The importance of developing Standard Operating Procedures (SOPs), maintaining sanitation, and controlling processing time and temperature was emphasized. Improving the understanding of HACCP among MSME actors is a key factor in effective hazard control and achieving food safety.Keywords: catfish floss; food safety; HACCP; hazard Abstrak: UMKM Suole merupakan salah satu produsen abon lele yang berupaya meningkatkan kualitas produk melalui penerapan Hazard Analysis Critical Control Point (HACCP). Penerapan dilakukan dengan penyusunan dan verifikasi diagram alir proses produksi abon lele, identifikasi bahaya, serta penetapan CCP dan batas kritis. Kegiatan pengabdian ini bertujuan memberikan wawasan dan pendampingan penerapan HACCP guna meningkatkan keamanan pangan, mutu, dan daya saing produk. Kegiatan dilaksanakan pada Oktober hingga Desember 2024 di UMKM Suole, meliputi wawancara, observasi lapangan, serta pendampingan dan analisis HACCP. Hasil kegiatan menunjukkan bahwa proses produksi abon lele mencakup beberapa tahap penting yang memerlukan pengawasan, seperti penerimaan bahan baku, pemisahan daging, penggorengan, dan pengemasan. Telah dilakukan identifikasi bahaya dan penetapan titik kendali kritis (CCP) untuk mencegah kontaminasi biologis, kimia, dan fisik. Selain itu, ditekankan pentingnya penyusunan SOP, sanitasi, serta pengendalian suhu dan waktu proses. Peningkatan pemahaman pelaku UMKM terhadap HACCP menjadi faktor kunci dalam pengendalian bahaya dan pencapaian keamanan pangan produk.Kata kunci: abon lele; bahaya; HACCP; keamanan pangan